محفزات النشاط الاقتصادي في الإسلام - بورزمة, وهیبة (University of eloued جامعة الوادي, 2015)
من خلال ھذه الدراسة قمت ببیان مفھوم المحفزات وأنواعھا وكذلك أھمیتھا بالنسبة للمجتمع في الإسلام وغیره مع بیان وجھ الاختلاف الموجود بین الإسلام والاقتصاد الوضعي وھذا تحت عنوان محفزات النشاط الاقتصادي في الإسلام. وركزت في ھذا الموضوع أیضا على دراسة مفھوم النشاط الاقتصادي في الإسلام والتركیز على أھم القطاعات المشروعة فیھ. والجزء الأھم في ھذه الدراسة أنني قمت بتسلیط الضوء على أثر المحفزات على النشاط الاقتصادي بكامل مجالاتھ وأسسھ المھمة، بعد أن قمت ببیان مفھوم كل أساس من ھذه الأسس التي لا یقوم النشاط الاقتصادي إلا بھا. و احتوت الدراسة على مقدمة تناولت فیھا أھم نقاط المنھجیة التي یجب إتباعھا للوصول إلى الطریق السلیم في البحث. وفي الأخیر توصلت في ھذه الدراسة إلى أھم النتائج وكان من أھم ھذه النتائج أن الدین الإسلامي یشجع ویحفز ویشجع الأفراد لتفعیل النشاط الاقتصادي أي أن للنشاط الاقتصادي مكانة مرموقة في الإسلام . This study intends to announce the concept of stimuli and their types, also their imp postures for the society in Islam and the other, and declaration the point of difference that is existed between Islam and lawful economy all this is entitled stimuli of economic act in Islam. In this research, Concentrate on the study of the concept of economic act in Islam and focusing on the most Important legal sectors on it . The most Important part in this study that I have highlighted, the effect of stimuli on the economic act by all its fields and an Important basics, after I have declared the concept of any basic that the economic act is got up . In the introduction, I agree the Important point of methodology that we must follow for reaching to the correct way in this research. Finally, I conclude many results, the most important one is that Islam encourages and motivates people for effecting the economic act. So, economic act haw remarkable place in Islam
مذكرة ماستر معاملات مالية
Keywords: محفزات/النشاط الاقتصادي/الإسلام; Motivations/Economic Activity/Islam